(untitled) (Experimental Student Experience, 2023)
This study aims to determine the implementation of zakat on agricultural products and the welfare of farmers in Bungtiang Village, Sakra Barat District. This research is a qualitative approach. Data collection techniques in this study used observation, interviews and documentation. Determination of informants in this study using triangulation. The informants in this study consisted of 1 expert informant and 5 main informants and 2 additional informants. The results showed that from a study of the implementation of agricultural zakat, it was found that most people were aware of the obligation to issue agricultural zakat, but still channeled their zakat in a traditional consumptive manner, so that the amount of zakat issued was not in accordance with Islamic law, farmers only issued zakat as much as 10 % using either irrigation water or rainwater. From a study of the economic welfare of the community, it has been able to meet the needs of dharuriyyat (hifzu-dien, hifzun-nafs, hifzun-’Aql, hifzun-nasl and hifzun-maal) and hajiyyat.